Smart choices a practical guide to making better decisions - Hammond. Jonh S. (Boston Harvard Business School Press, 1999)
Making smart choices is a fundamental life skill, relevant to every one: business people, doctors, lawyers, teachers, students, parents, young, old. Your decisions shape the course of your professional career and the quality of your personal life. Yet few people learn real decision making skills. Consequently we approach our choices tentatively, or even fearfully, and avoid giving decisions the time and thought required to turn them to our best advantage. Smart Choices offers the first straightforward, easy-to-follow process designed to improve the way you make business decisions, family decisions, personal decisions-any decision that can help you reach your goals. Authors Hammond, Keeney, and Raiffa, among the world's best-known experts on resolving complex decision problems, have created a user-friendly set of techniques for assessing your options more clearly and effectively, ultimately empowering you to make smarter choices. Their step-by-step procedures combine solid research with practical experience and common sense to help you specify your objectives, identify creative alternatives, make reasoned tradeoffs, clarify uncertainties, and evaluate the risks. Smart Choices doesnt tell what to decide; it tells you how.
Keywords: Decision making